2017
DOI: 10.1002/prp2.345
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance study on the tolerability and safety of Flebogamma®DIF (10% and 5% intravenous immunoglobulin) in adult and pediatric patients

Abstract: Direct comparisons of tolerability and safety of concentrated intravenous immunoglobulin (IVIG) versus less concentrated products are scarce. In this postauthorization, prospective, observational, multicenter study, a systematic comparison of 10% and 5% concentrations of Flebogamma® DIF IVIG was performed in both adult and pediatric patients treated with the studied IVIG products according to the approved indications under routine conditions. Dose of product administered, adverse events (AEs), physical assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The percentage of dropouts (28%) over a period of 14 months (55 weeks) was similar to that reported elsewhere (13.5% to 31.3%), 7‐10,12 but was higher in the two IVIG arms (34.6%‐34.9%) and lower in the other arm and placebo, both without IVIG (20.0%‐21.8%), which is consistent with the safety profile reported in patients receiving infusions of albumin and IVIG 43,44 . In addition, only two (0.6%) patients died during the study, which is similar to the low mortality rates reported elsewhere (1.3%‐2.5%) 8‐10,12 .…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of dropouts (28%) over a period of 14 months (55 weeks) was similar to that reported elsewhere (13.5% to 31.3%), 7‐10,12 but was higher in the two IVIG arms (34.6%‐34.9%) and lower in the other arm and placebo, both without IVIG (20.0%‐21.8%), which is consistent with the safety profile reported in patients receiving infusions of albumin and IVIG 43,44 . In addition, only two (0.6%) patients died during the study, which is similar to the low mortality rates reported elsewhere (1.3%‐2.5%) 8‐10,12 .…”
Section: Discussionsupporting
confidence: 89%
“…However, serious headaches requiring hospitalization are uncommon [11]. Overall, the surveillance study reported that the products were safe and well tolerated [10]. In the present study, no new safety concerns were identified, and the safety profile remained consistent with the known adverse effects of IVIG treatment.…”
Section: Discussionsupporting
confidence: 62%
“…These included an episode of severe headache in two patients which were considered to be possibly related to the study drug, as expected for IVIG treatment. A surveillance study on the tolerability and safety of Flebogamma R DIF (10 and 5% IVIG) in adult and pediatric patients found that the most frequent treatment-related AEs were headache and pyrexia [10]. However, serious headaches requiring hospitalization are uncommon [11].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that IVIG products are generally deemed safe and welltolerated. Most of their adverse effects are mild and transient [25].…”
Section: Discussionmentioning
confidence: 99%